To find both f(8) and f(-5), we will need to plug in their values for x and solve for each. Then, we can subtract them to find the final answer.
Finding f(8):
f(8) = 3(8) - 2
f(8) = 24 - 2
f(8) = 22
Finding f(-5):
f(-5) = 3(-5) - 2
f(-5) = -15 - 2
f(-5) = -17
Subtracting f(8) and f(-5):
f(8) - f(-5)
22 - - 17
22 + 17
39
Hope this helps!! :)
X=12
0.75x + 5=14
Take away 5 on both sides
So 0.75x +5-5=14-5
0.75x=9
0.75x divided by 9 = 12
Answer:
-6/5
Step-by-step explanation:
-5-1 / 0-(-5)
2 + 7 - 9 + 11
= 9 - 9 + 11
= 0+ 11
= 11
hope it's helpful !
have a nice day :)
Answer:
0 = (3-2x) x (x x 2 -5)
(3-2x) x ( x x 2 - 5) = 0
(3-2x) x (2x - 5) = 0
3 - 2x = 0
2x - 5 = 0
x = 3/2
x = 5/2
x1 = 3/2 or x2 = 5/2